Unravelling Psychological Ramifications of Gender-Based Violence against Male Lecturers in Rural Universities of Zimbabwe - Munyaradzi Chidarikire; Juliet Kamwendo (E-Journal of Humanities, Arts and Social Sciences)
This paper explored the psychological consequences of gender-based violence against male lecturers in rural Universities in Zimbabwe. Gender-based violence is a deeply rooted issue in Zimbabwe, affecting both women and male lecturers. Unfortunately, the gender-based violence against males especially university lecturers is unreported or underreported. Using a qualitative approach, the study employed purposive sampling to select 16 participants based on criteria such as gender, age, expertise, and experiences related to the topic. Data was collected through focus group discussions and interviews, while content thematic analysis was used for data analysis. One of the findings of this study indicated that a significant number of Zimbabwean male lecturers in rural Universities of Zimbabwe are experiencing gender-based violence, resulting in various problems, including stress. Consequently, the participants of the study recommended that rural male lecturers should seek counselling to address the psychological impact of gender-based violence on their overall well-being. Through examining the psychological consequences of GBV against men, this study seeks to contribute to a comprehensive understanding of the effects of gender-based violence on individuals, regardless of their gender. The findings of this research are expected to inform the development of targeted interventions and support services that address the specific needs of male survivors of GBV in rural Zimbabwe.